Kebijakan berorientasi ganda pada industri kelapa sawit: Antara visi kerakyatan dan efisiensi - Suseno, Priyonggo (Economic Journal of Emerging Markets, 2016)
Crude Palm Oil industry is one of the mature industrial sectors in Indonesia. This industry has been growing since 1939. Unfortunately, this industry still could not grow steadily although government has give incentives to this industry/ The profitable exchange rate (FOB price) of CPO could not raise the export volume.